Biomolecular DNP‐Supported NMR Spectroscopy using Site‐Directed Spin Labeling. Issue 37 (7th September 2015) - van der Cruijsen, Elwin A. W.; Koers, Eline J.; Sauvée, Claire; Hulse, Raymond E.; Weingarth, Markus; Ouari, Olivier; Perozo, Eduardo; Tordo, Paul; Baldus, Marc
Abstract Dynamic nuclear polarization (DNP) has been shown to greatly enhance spectroscopic sensitivity, creating novel opportunities for NMR studies on complex and large molecular assemblies in life and material sciences. In such applications, however, site‐specificity and spectroscopic resolution become critical factors that are usually difficult to control by current DNP‐based approaches. We have examined in detail the effect of directly attaching mono‐ or biradicals to induce local paramagnetic relaxation effects and, at the same time, to produce sizable DNP enhancements. Using a membrane‐embedded ion channel as an example, we varied the degree of paramagnetic labeling and the location of the DNP probes. Our results show that the creation of local spin clusters can generate sizable DNP enhancements while preserving the intrinsic benefits of paramagnetic relaxation enhancement (PRE)‐based NMR approaches. DNP using chemical labeling may hence provide an attractive route to introduce molecular specificity into DNP studies in life science applications and beyond.